The powers of the Labour Court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration : a comparative study - Bezuidenhout, Susan Antoinette (University of South Africa, 2004)
A critical and in-depth discussion of the powers of the labour court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration, the application of the author's findings relating to common-law, legislation and case law and a critical analysis thereof. Special reference is made to the provisions of sections 145 and 158(1)(g) of the Labour Relations Act 66 of 1995 including, in particular, the alternative application thereof in practice and scope for improvement in order to address potential prejudice to parties occasioned by the compulsory nature of (certain) dispute resolutions. This thesis incorporates a comparative study of the British and German labour law systems with reference to the relevant appeal and/or review procedures (as applied in their tribunals/courts), together with a discussion and application of certain other provisions relevant to South Africa labour law.
Keywords: British Labour system; CCMA; Compulsory arbitration; Dispute resolution; German Labour system; Labour Court; Review procedure

Concurrence et sous- tarification des risques : Quelles solutions pour éradiquer ce fléau sur le marché togolais des assurances - Alognon-Anani, Akoété (Institut International des Assurances (IIA), 2004)

le marché financier régional et le secteur des assurances : Cas du Bénin - Andjinou Ahoua, Marcel Raoul Koffi (Institut International des Assurances (IIA), 2004)

La réquisition et l'affrètement des navires marchands par les armées - Bertin, Damien (Aix-Marseille Université, 2004)

Les conférences maritimes et le droit de la concurrence communautaire - Besançon, Marion (Aix-Marseille Université, 2004)

Image de marque de l'assurance au Cameroun : Solution à mettre en œuvre pour son amélioration - Bessala, Francois-Xavier (Institut International des Assurances (IIA), 2004)

L'incendie à bord du navire marchand - Beuzit, Sébastien (Aix-Marseille Université, 2004)

Les pavillons et registres bis en Europe - Binon-Davin, Stéphanie (Aix-Marseille Université, 2004)

Les problèmes de tarification et d'étude des risques en matière d'assurance - Boukamba, Jean Paul (Institut International des Assurances (IIA), 2004)

La politique communautaire des transports - Catalan, Sophie (Aix-Marseille Université, 2004)

Le projet d'instrument de la CNUDCI sur le transport multimodal transmaritime - Chaillé de Néré, Dixie (Aix-Marseille Université, 2004)

Confection et analyse de l'état C9 de l'union des assurances du Burkina IARDT - Compaore, Antoine (Institut International des Assurances (IIA), 2004)

La problématique des arrières de primes du marché Burkinabe de l'assurance : Cas de la SONAR-IARD - Dabire, Beynir Narcisse (Institut International des Assurances (IIA), 2004)

Le remorquage des plates-formes pétrolières - de Prunelé, Amélie (Aix-Marseille Université, 2004)

La gestion des risques portuaires : Le cas du port autonome de Dakar (PAD) - Dioume Mountaga, Tall (Institut International des Assurances (IIA), 2004)

Traitement technique et financier des opérations de réassurance au sein de l'UCAR (centrafrique) - Dodessa, Nesmy-Ledoux (Institut International des Assurances (IIA), 2004)

Les avaries communes : place actuelle d'une institution antique - Dusserre, Cédric (Aix-Marseille Université, 2004)

L'harmonisation du certificat d'assurance maritime sur le marché camerounais : Incidence sur le développement de la branche transport - Ediba, Simon Pierre (Institut International des Assurances (IIA), 2004)

Le droit pénal maritime - Essou, Michel (Aix-Marseille Université, 2004)

Les transports internationaux de marchandises par mer non soumis aux règles de la Haye-Visby - Gacon, Pierre-Paul (Aix-Marseille Université, 2004)

La responsabilté pénale du transporteur routier - Garofalo, Ludovic (Aix-Marseille Université, 2004)

Audit de la solvabilité de la mutuelle agricole de Côte d'Ivoire (MACI) - Gnizako Euloge, Hervé (Institut International des Assurances (IIA), 2004)

Les droits des passagers dans le transport maritime : l'incidence du droit de la consommation sur la protection des passagers - Grach, Laure (Aix-Marseille Université, 2004)

Les navires inférieurs aux normes - Hagry, Alexandre (Aix-Marseille Université, 2004)

Les nouveaux canaux de distribution des produits d'assurances dans l'espace CIMA : Cas du Mali - Karembe, Allaye (Institut International des Assurances (IIA), 2004)

Le contrôle de gestion dans l'optimisation des résultats d'une société d'assurances-IARD - Koffi, Masé Elom Assignon (Institut International des Assurances (IIA), 2004)

Contribution à la mise en place d'une structure de contrôle de gestion dans une entreprise d'assurances : Cas de ACTIVA Assurances - Korbol, Firmin (Institut International des Assurances (IIA), 2004)

Analyse technique et financière des comptes d'une société d'assurance vie : cas de LMAI vie - Kouadio, Konan Eugène (Institut International des Assurances (IIA), 2004)

La loi applicable au contrat de transport maritime - Lincoln, Jérémy (Aix-Marseille Université, 2004)

Procédure et méthode de contrôle des intermédiaires : Cas des assurances Générales du Congo (AGC) - Mabiala, Aimé Sulpice Doctrové (Institut International des Assurances (IIA), 2004)

la problématique de la collaboration des agents généraux avec les sociétés d'assurances : Cas des assureurs conseils tchadiens avec la société tchadienne d'assurances et de réassurances - Madjita Noa Samngar, René (Institut International des Assurances (IIA), 2004)

La réforme de la politique commune de la pêche - Mazel, Stépahen (Université Paul Cézanne Aix-Marseille 3, 2004)

Le recours subrogatoire en assurance maritime de facultés - Mekadmi, Djamila (Aix-Marseille Université, 2004)

Le facteur humain dans la sécurité maritime - Merbouh, Kaoutar (Aix-Marseille Université, 2004)

Comptabilisation des comptes techniques et financiers de réassurance dans une société d'assurances IARD : Cas des assurances Générales du Congo (AGC) - Mouambouma, Richard Bienuenu (Institut International des Assurances (IIA), 2004)

Etude contributive sur la mise en place d'un pool TPV au Cameroun et son incidence dans l' équilibre de la branche automobile - Ngouh, Félix (Institut International des Assurances (IIA), 2004)

Concurence et sous-tarification des risques : Solutions pour éradiquer ce fléau des marchés d'assurances - Okevayi Ngayila, Symphorien (Institut International des Assurances (IIA), 2004)

la problématique des impayés et la réglementation sur la couverture des engagements réglementés des sociétés d'assurances de dommages : Cas du marché Beninois - Ousmane, Adéwalé Laguide (Institut International des Assurances (IIA), 2004)

Les limites de l'intégration régionale internationale : le cas de la Communauté économique des États de l'Afrique de l'Ouest (CEDEAO) - Ramdé, Mamadou (Université de Montréal, 2004)
Mémoire numérisé par la Direction des bibliothèques de l'Université de Montréal.
Keywords: Afrique Occidentale française; Afrique de l'Ouest; Communauté économique; Conflits ethniques; Coopération; Démocratie; Désertification; Développement régional; Environnement; Immigration; Intégration; Organisations intergouvernementales; Sous-développement; Tiers-monde; Union monétaire

Le transport de marchandises dangeureuses - Ravier, Laetitia (Aix-Marseille Université, 2004)

Les lieux de refuge - Rivier, Stéphane (Aix-Marseille Université, 2004)

Météorologie et droit maritime - Sevestre, Paul-Ambroise (Aix-Marseille Université, 2004)

la gestion d'un dossier sinistre en assurance des facultés maritimes - Soumare, bassirou (Institut International des Assurances (IIA), 2004)

Le rôle du courtier d'assurances maritimes - Spaccesi, Laurent (Aix-Marseille Université, 2004)

Art Saigon : un petit chargeur au coeur du commerce maritime - Torck, Laurent (Aix-Marseille Université, 2004)

Les aides à la navigation maritime - Vieuxbled, Jean-Pierre (Aix-Marseille Université, 2004)

La distribution de l'assurance santé par l'intermédiaire du courtage - Yombo, Daniel Honoré (Institut International des Assurances (IIA), 2004)

Le rôle des sociétés de classification : l'exemple du Bureau Veritas - Zavoreo, Željana (Aix-Marseille Université, 2004)

Les nouveaux canaux de distribution des produits d'assurances IARD : Cas du Bénin - Zinsou, Assiba Léontine (Institut International des Assurances (IIA), 2004)